Hypertension for the clinician - Robertson J.Ian S. (London W.B. Saunders Company, 1994)
Gives guidance on assessment, diagnosis and management of hypertension, including 23 case studies which take the clinician through case management. The book contains a comprehensive drug appendix, as well as the International Guidelines and a critical assessment of them.